Toll-Like Receptor-1 and Receptor-2 and Beta-Defensin in Postcholecystectomy Bile Duct Injury - Alejandra Guillermina Miranda-Díaz; José Manuel Hermosillo-Sandoval; Martha Arisbeth Villanueva-Pérez; Luis Miguel Román-Pintos; Trinidad García-Iglesias; Adolfo Daniel Rodríguez-Carrizalez; Ernesto Germán Cardona-Muñoz (Gastroenterology Research and Practice)
Postcholecystectomy bile duct injuries (BDI) produce hepatic cholestasis and cause infection of the biliary tract. The biliary cells participate in secreting cytokines and in expression of immune response receptors. Toll-like receptors (TLRs) conduct signalling and activate the innate and adaptive inflammatory response. The objective was to determine the serum levels of TLR-2 and the expression of TLR-1 and TLR-2 and β-defensin in liver biopsies of postcholecystectomy BDI patients. A transverse, analytical study with 2 groups was done. One group included healthy volunteers (control group) and other included 25 postcholecystectomy BDI patients with complete biliary obstruction. Using the Enzyme-linked Immunosorbent Assay (ELISA) technique, serum levels of TLR-2 were determined, and with immunofluorescence the morphologic analysis of TLR-1 and TLR-2 and β-defensin in liver biopsies of postcholecystectomy BDI patients was performed. The average TLR-2 serum level in the control group was 0.0 pg/mL and in the BDI group, 0.023±0.0045 pg/mL (P<0.0001, bilateral Mann Whitney U). Immunofluorescence was used to determine the expression in liver biopsies, blood vessels, bile ducts, and hepatic parenchyma where 12 hepatic biopsies were positive for TLR-1 with average of 3213057.74±1071019.25 μm2; and 7 biopsies were positive for β-defensin with an average of 730364.33±210838.02 μm2; and 6 biopsies positive for TLR-2, obtaining an average of 3354364.24±838591.06 μm2. In conclusion, TLR-1 and TLR-2 and β-defensin play an important role in the innate antimicrobial defense of the hepatobiliary system.